Sm3+ Doped Borotellurite Glass: Absorption, Fluorescence and Optical Parameters - Độ, Phan Văn (VNU Journal of Science: Mathematics - Physics, 2018)
Borotellurite glasses doped with Sm 3+ ions were prepared by a melt–quenching technique. The studies on optical characterization of Sm 3+ ions have been carried out through absorption, emission and decay spectra. Judd-Ofelt (JO) intensity analysis has been presented and JO parameters were calculated for Sm 3+ ions in borotellurite glasses. Radiative properties such as transition probabilities, branching ratios, radiative lifetime of 4 G 5/2 level and quantum efficiency were estimated by using JO parameters.